Micromedia & e-Learning 2.0: Gaining the Big Picture Proceedings of Microlearning Conference 2006 - Hug, Theo; Lindner, Martin; Bruck, Peter A. (innsbruck university press, 2006)
Micromedia & e-Learning 2.0 brings together media technologists and academics, visionaries and practitioners, entrepreneurs and corporate professionals from around the world to address central questions at the interface of emerging technologies, future trends of distributing learning and models of knowledge organization. How will e-learning change in the context of semantic web developments? Which patterns derive from microcontent based activities and technologies? How do learning cultures and habits alter in the context of seemingly stable institutions, Web 2.0 and mobile telephony? What are the impacts of micromedia dynamics in terms of symbolic, technological and societal formations of education, communication, knowledge dynamics, economy and politics? The Proceedings of Microlearning Conference 2006 work to answer these questions, rethinking concepts of formability, granularity, interactivity, individual use and joint practice in new media ecologies. - Micromedia & e-Learning 2.0 versammelt Medientechnologen und Akademiker, Visionäre und Praktiker, Unternehmer und unternehmerische Professionelle aus der ganzen Welt, um sich mit zentralen Fragen an der Schnittstelle von neu entstehenden Technologien, Zukunftstrends dezentralisierten Lernens und Modellen der Wissensorganisation zu befassen. Wie wird sich e-Learning im Kontext von semantischen Webentwicklungen verändern? Welche Muster stammen von auf Mikrolernen basierenden Aktivitäten und Technologien? Wie verändern sich Lernkulturen und -gewohnheiten im Kontext von scheinbar stabilen Institutionen, Web 2.0 und Mobilfunk? Was sind die Auswirkungen der mikromedialen Dynamik hinsichtlich symbolischer, technologischer und gesellschaftlicher Strukturen von Bildung, Kommunikation, Wissensdynamik, Wirtschaft und Politik?